Muhammad : A Story of God's Messenger and the Revelation that Changed the World - Chopra, Deepak (New York HarperOne, 2011)
Born into the factious world of war-torn Arabia, Muhammad's life is a gripping and inspiring story of one man's tireless fight for unity and peace. In a world where greed and injustice ruled, Muhammad created change by affecting hearts and minds. This title focuses on the life of Muhammad.
Keywords: Muḥammad, Prophet, -632 -- Muslims -- Islam